Development of gluten with immunomodulatory properties using mTG-active food grade supernatants from Streptomyces mobaraensis cultures. (July 2017) - Treppiccione, Lucia; Ottombrino, Antonio; Luongo, Diomira; Maurano, Francesco; Manteca, Ángel; Lombó, Felipe; Rossi, Mauro
Highlights: A treatment of wheat flour with Streptomyces mobaraensis mTG-active supernatant was developed. The treatment induced solubilisation of both gliadin and glutenin. Solubilised gliadin showed immunomodulatory properties in vitro . Bread manufactured with treated flour had only minor changes in baking parameters. The new technology might have implications for Coeliac disease management. Abstract: Transamidation by microbial transglutaminase (mTG) blocks gliadin immunotoxicity in Coeliac disease (CD), however, mTG is expensive and limits cost effectiveness. Herein, we set up an inexpensive treatment by employing culture supernatant of Streptomyces mobaraensis . A food-grade medium and fermentation workflow were developed to obtain inexpensive mTG (2.6 U/ml at 120 h). Incubation of wheat flour with culture supernatant and lysine ethyl ester solubilised both gliadin and glutenin, similarly to the process using commercial mTG. The water-soluble protein fraction (spfcs ) cross-reacted against gliadin, as it stimulated gliadin-specific spleen cells from HLA-DQ8 transgenic mice, a model of gluten sensitivity. Notably, splenocytes from spfcs -immunised mice induced high levels of anti-inflammatory IL-10 when challenged with gliadin. Bread manufactured with treated flour had only minor changes in the baking parameters. In conclusion, our data highlighted the immunomodulatory properties of a bread produced by applying this protocol, with implications for the management of CD patients.